Development of Augmented Reality in Islamic Religious Education as an Anti-Corruption Learning Medium - Chamami, M. Rikza; Nasikhin, Nasikhin; Saefudin, Ahmad (IAIN Ponorogo, 2022)
This study aims to develop and determine the impact of using augmented reality as an anti-corruption educational medium based on the development of Islamic educational materials. The data processing used to research and development methods ADDIE model using a validity test and measurements of N-Gain scores. Three junior high schools with different environmental characteristics participated in the study. The findings first indicate that the development of augmented reality for the field of anti-corruption education can be adapted to the essential competencies of Islamic Religious Education subjects with the themes of honesty, trustworthiness, and istiqomah. Second, there was an increase in the cognitive domain, as indicated by the anti-corruption education values for SMP N 02 Bawang students by 79.5%; SMP N 01 Subah students by 79%; and SMP N 01 Batang students by 80.44%. On the N-Gain scale, all three achievements are considered effective. This research has implications for demonstrating that the application of augmented reality can effectively improve cognitive ability in anti-corruption education based on the development of Islamic educational materials. We recommend that these findings be used as a basis for determining anti-corruption education policies in Indonesia